Auf dem Weg zu Souveränität und Westintegration (1948-1955) Der Beitrag des Völkerrechtlers und Diplomaten Wilhelm Grewe - Lambertz-Pollan, Ruth (Studien zur Geschichte des Völkerrechts, 2016)
Wilhelm Grewe (1911-2000) began his career as a professor of international law under the Third Reich. In the immediate postwar period, he already strongly advocated a legal framework for relations between the Occupying Powers and Germany. In 1951, Konrad Adenauer entrusted him with the negotiations on the General Treaty on Germany ("Deutschlandvertrag"). This case study, the first on Wilhelm Grewe, analyses his influence on the negotiations on the sovereignty and Western integration of the Federal Republic during the period from 1948-55. The study particularly highlights the practicalities of day-to-day operations and decision-making processes at the advisory level. It also assesses Grewe's scope for action at the national and international levels. Another key element in evaluating his influence is the interaction between policy and international law. The author is Maître de conférences at the University of Nantes.